Ultrasound-guided superficial serratus plane block in dog cadavers: an anatomical evaluation and volume dispersion study. (January 2020) - Freitag, Flavio AV.; Gaio, Thalise S.; dos Santos, Amanda AM.; Muehlbauer, Eloisa; Machado, Marcello; Duque, Juan CM.
Abstract: Objective: To evaluate the anatomy of the serratus plane in dogs to establish the optimal landmarks for a superficial serratus plane (SSP) block and evaluate ropivacaine–methylene blue solution dispersion with three volumes of injection. Study design: Prospective experimental cadaveric study. Animals: A formaldehyde solution-preserved dog cadaver and 15 frozen/thawed adult dog cadavers. Methods: The thoracic wall of the formaldehyde-preserved cadaver was dissected. An SSP injection was performed on each hemithorax of the cadavers, with the ultrasound transducer placed over the fourth and fifth ribs, at the level of the shoulder joint. A needle was inserted in-plane in a caudocranial direction until it could be visualized between the serratus ventralis thoracis and latissimus dorsi muscles. Dog cadavers were injected with a ropivacaine–methylene blue solution at 0.3, 0.6 and 1.0 mL kg –1 and were dissected to determine the spread of the dye. Results: The thoracic wall muscles identified in the formalinized cadaver were the cutaneous trunci, latissimus dorsi, external abdominal oblique, serratus ventralis thoracis, scalenus, serratus dorsalis cranialis and external intercostal. The nerves identified in the SSP included the lateral cutaneous branches of intercostal nerves, intercostobrachial nerves and long thoracic nerve. The solution was successfully injected at the SSP in 26 of 29 (89.7%) attempts. Dermatomal dye spread, median (range), was 4 (3–6), 4 (2–5) and 5 (4–8) for 0.3, 0.6 and 1.0 mL kg –1, respectively, with no significant difference among them. Conclusions and clinical relevance: Injections for an SSP block were easily performed under ultrasound guidance, using the fourth and fifth ribs at the level of the shoulder joint as reference landmarks. An injected volume of 0.3 mL kg –1 may be sufficient for hemithorax analgesia in dogs. Further studies in dogs are required to determine the utility of this technique.